From Missionary Translation to Local Theological Inquiry: A Narrative History of the Lisu Bible. (August 2019) - Arrington, Aminta
Abstract : The Lisu are a largely Christian minority group in south-west China who, as an oral culture, express their faith more through a set of Christian practices done as a group and less through bible reading as individuals. Even so, the Lisu practice of Christianity specifically, and Lisu culture more generally, was profoundly impacted by the written scriptures. During the initial evangelisation of the Lisu by the China Inland Mission, missionaries created a written script for the Lisu language. Churches were constructed and organised, which led to the creation of bible schools and the work of bible translation. In the waves of government persecution after 1949, Lisu New Testaments were hidden away up in the mountains by Lisu Christians. After 1980, the Lisu reclaimed their faith by listening to the village elders tell the Old Story around the fires and reopening the churches that had been closed for twenty-two years. And they reclaimed their bible by retrieving the scriptures from the hills and copying them in the evening by the light of a torch. The Lisu bible has its own narrative history, consisting of script creating, translating, migrating, and copying by hand. At times it was largely influenced by the mission narrative, but at other times, the Lisu bible itself was the lead character in the story. Ultimately, the story of the Lisu bible reflects the Lisu Christian story of moving from missionary beginnings to local leadership and, ultimately, to local theological inquiry.